2020
DOI: 10.2147/cmar.s255787
|View full text |Cite
|
Sign up to set email alerts
|

<p>MicroRNA-421 Inhibits Apoptosis by Downregulating Caspase-3 in Human Colorectal Cancer</p>

Abstract: Dysregulated microRNAs (miRNAs/miRs) have been reported to play significant roles in pathogenesis of colorectal cancer (CRC). Previous studies have demonstrated that miR-421 regulates apoptosis in some cancers. Caspase-3 plays a key role in apoptosis, but the relationship between miR-421 and caspase-3 in CRC has not been determined. In this study, we investigated the role of miR-421 in CRC and the relationship between miR-421 and caspase-3. Methods: Expression of miR-421 and caspase-3 were detected in human pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 39 publications
(46 reference statements)
0
7
0
Order By: Relevance
“…miR-224, miR-147b, and miR-31 are related to lymph node metastasis and prognosis in LUAD [46]. Recently, miR-421 was found to be dysregulated in breast and colon tumors [47,48].It has been reported that miR-421 promotes the development of osteosarcoma by regulating the target gene MCPIP1 and that it might serve as a valuable biomarker in patients with esophageal adenocarcinoma and osteosarcoma [49][50][51]. Chen et al found that overexpression of plasma miR-421 can act as a novel biomarker for the detection of precancerous lesions and early gastric cancer [52].…”
Section: Discussionmentioning
confidence: 99%
“…miR-224, miR-147b, and miR-31 are related to lymph node metastasis and prognosis in LUAD [46]. Recently, miR-421 was found to be dysregulated in breast and colon tumors [47,48].It has been reported that miR-421 promotes the development of osteosarcoma by regulating the target gene MCPIP1 and that it might serve as a valuable biomarker in patients with esophageal adenocarcinoma and osteosarcoma [49][50][51]. Chen et al found that overexpression of plasma miR-421 can act as a novel biomarker for the detection of precancerous lesions and early gastric cancer [52].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to miRNA playing fundamental roles in inflammation, many miRNAs are also implicated in regulating cell survival. Both miR-23a and miR-421, for example, repress caspase-9 and caspase-3, respectively [ 216 , 217 ]. miR-421 is downregulated in response to smoke [ 191 ], whereas the activity of caspase-3 is increased by smoke exposure [ 218 ].…”
Section: Post-transcriptional Regulation In Copdmentioning
confidence: 99%
“…(Bian et al 2018) microRNAs (miRNAs) are a class of single-stranded, short, and conserved ncRNAs 18 ± 24 nucleotides in length that negatively modulate gene expression at the post-transcriptional level by binding to the 3untranslated region (3 UTR) of target genes. (Zhou et al 2020) Several studies have suggested that miRNAs regulate many physiological processes in the cell, including migration, invasion, cell proliferation, and apoptosis. Aberrant miRNAs also participate in the initiation, promotion, angiogenesis, metastasis, and drug resistance of several types of cancers.…”
Section: Introductionmentioning
confidence: 99%